R code and data for "Comparing multiple survey and recruitment-mortality models to assess growth rates and population projections" - Severud, William J; DelGiudice, Glenn D; Bump, Joseph K (2017)
See ReadMe text file for a comprehensive description of all uploaded data files. This collection of files provides data and R code supporting the publication "Comparing survey and multiple recruitment-mortality models to assess growth rates and population projections" in Ecology and Evolution. We provide all necessary data not included in the manuscript to reproduce the analysis of growth rates and population projections of moose in northeastern Minnesota. Minnesota Environmental and Natural Resources Trust Fund Wildlife Restoration (Pittman-Robertson) Program Minnesota Department of Natural Resources Section of Wildlife’s Wildlife Populations and Research Unit Minnesota Deer Hunters Association National Science Foundation NSF ID#1545611 National Science Foundation NSF ID#1556676